Design of Visible Light Response Anatase TiO2: Codoping with Transition Metals and Interstitial Carbon - Chen, Shou-Gang; Ma, Zhen-Qing; Yu, Mei-Yan; Sun, Wei-Wei (Asian Journal of Chemistry, 2014)
Interstitial carbon and metal codoped TiO2 were theoretically studied and explaining the presence of two optical absorption thresholds in most the experiments. To bond the extra electron of interstitial carbon, we proposed the codoping system with transition metals and interstitial carbon atoms, and suggested that interstitial carbon with the nearest titanium substituted by vanadium codoped TiO2 is a strong candidate for the visible light sensitive photocatalysts, with strong response absorption in both ultraviolet region and visible light region, based on the formation energy calculation and fully occupied hybridized states in the midgap.